Civil society contributions to local level flood resilience: Before, during and after the 2015 Boxing Day floods in the Upper Calder Valley. Issue 2 (30th November 2018) - Forrest, Steven; Trell, Elen‐Maarja; Woltjer, Johan
Abstract : There is an increasing emphasis on the local level as well as growing expectations regarding civil society actors in flood‐risk management in the UK. However, not enough is known about the potential contributions of civil society to flood resilience at the local level. This paper addresses this knowledge gap by conceptualising flood resilience at the local level across three phases inherent to flood disasters: pre‐flood, during the flood and post‐flood. These phases act as the foundation for this paper's exploration of the contributions of civil society to local‐level flood resilience. Data were collected before, during and after the 2015 Boxing Day floods through interviews (in 2015 and 2017) and from secondary data sources. The paper identifies the importance of time and place when analysing civil society contributions to local level flood resilience. These contributions were dynamic over time with a strong initial response that diminished over time due to apathy, "active forgetting" and lack of further exposure. Exposure and a sense of community strongly influenced civil society contributions to flood resilience in the Upper Calder Valley. Issues of representation and varying place‐based capacities were also identified as relevant for flood resilience‐based policies. These results have larger implications for our understanding of the contributions of civil society actors to flood resilience and suggest that while they can deliver better local context‐specific approaches, there needs to be caution over the long‐term sustainability and longevity of their contributions. Abstract : The paper focuses on before, during and after the 2015 Boxing Day floods in the Upper Calder Valley, England. Civil‐society contributions to local level flood resilience are explored in this paper through three phases inherent to flood disasters: pre‐flood, during the flood and post‐flood. These results have larger implications in our understanding of the contributions of civil society actors to flood resilience and suggest that while they can deliver better local context‐specific approaches, there needs to be caution over the long‐term sustainability and longevity of their contributions.